Length-weight relationship (LWR) of mud crabs (Scylla sp.) in mangrove waters Peukan Bada Aceh Besar as the basic for waters resources development. Issue 1 (February 2021) - Nurfadillah, N; Silvia, N; Octavina, C; Dewiyanti, I; Rizwan, T
Abstract: Mud crab ( Scylla sp.) is one of the aquatic resources that has high economic value so that the information on length-weight relationships is important for sustainable fisheries management. The objectives of this study were to determine the abundance of mud crab ( Scylla sp.), the sex ratio of mud crab ( Scylla sp.) and to analyze the length-weight relationship of mud crabs ( Scylla sp.). This study was conducted in April 2019. Sampling of mud crabs ( Scylla sp.) was carried out by using a bubu crab trap with the random sampling method. The bubu size is in length 47 cm, width 31 cm and height 19 cm. The sampling at ach station was repeated three times during low tide conditions. Sampling location was determined by using the stratified random sampling method. The results of the analysis showed that sampled number of mud crabs ( Scylla sp.) in the mangrove waters of Peukan Bada were 90 individu, consisting of 50 ind female mud crabs and 40 ind male mud crabs. Therefore, sex-ratio in mud crabs ( Scylla sp.) shows that the sex ratio between male and female individuals is still in a balanced state. The growth pattern were negative allometric (b<3), which means that the growth pattern of carapace length is faster than the body weight of mud crabs. The results also showed that the correlation coefficient (r) values for male and female mud crabs were 0.89 and 0.94, respectively. This indicates a close relationship between length and weight of mud crabs. Environmental parameter factors such as salinity and temperature greatly affect the growth pattern of mud crabs and sex ratio in the mangrove waters Peukan Bada, Aceh Besar.